Clinical improvement in psoriasis with specific targeting of interleukin-23 - Kopp, Tamara; Riedl, Elisabeth; Bangert, Christine; Bowman, Edward P.; Greisenegger, Elli; Horowitz, Ann; Kittler, Harald; Blumenschein, Wendy M.; McClanahan, Terrill K.; Marbury, Thomas; Zachariae, Claus; Xu, Danlin; et al. (Nature (London), 2015)
A proof-of-concept phase I clinical trial demonstrates that targeting interleukin (IL)-23 with an antibody that binds to the p19 subunit leads to clinical improvement of disease in patients with moderate to severe psoriasis. Antibody treatment of psoriasis Sauzanne Khalilieh and colleagues report a proof-of-concept phase I clinical trial which demonstrates that targeting the pro-inflammatory cytokine interleukin-23 (IL-23) with tildrakizumab, an antibody that binds to the p19 subunit of IL-23, leads to symptomatic improvement of disease in patients with moderate to severe psoriasis. The antibody is well tolerated, suggesting that selective targeting of IL-23 merits further study. Psoriasis is a chronic inflammatory skin disorder that affects approximately 2–3% of the population worldwide and has severe effects on patients’ physical and psychological well-being 1 , 2 , 3 . The discovery that psoriasis is an immune-mediated disease has led to more targeted, effective therapies; recent advances have focused on the interleukin (IL)-12/23p40 subunit shared by IL-12 and IL-23. Evidence suggests that specific inhibition of IL-23 would result in improvement in psoriasis. Here we evaluate tildrakizumab, a monoclonal antibody that targets the IL-23p19 subunit, in a three-part, randomized, placebo-controlled, sequential, rising multiple-dose phase I study in patients with moderate-to-severe psoriasis to provide clinical proof that specific targeting of IL-23p19 results in symptomatic improvement of disease severity in human subjects. A 75% reduction in the psoriasis area and severity index (PASI) score (PASI75) was achieved by all subjects in parts 1 and 3 (pooled) in the 3 and 10 mg kg −1 groups by day 196. In part 2, 10 out of 15 subjects in the 3 mg kg −1 group and 13 out of 14 subjects in the 10 mg kg −1 group achieved a PASI75 by day 112. Tildrakizumab demonstrated important clinical improvement in moderate-to-severe psoriasis patients as demonstrated by improvements in PASI scores and histological samples.